The Tourism Management Based on the Social Capital of Ethnic Communities in Maesalong-Nok Sub-district, Mafah Luang District, Chiang Rai Province - Chumpa, Natthida; Techathammawong, Taweechoke (Journal of Cultural Approach, 2021)
This research aimed to analyze the potential of tourism management based on the ethnic community’s capital and to investigate the ways in developing community-based tourism management. This mixed-method study applying structured interviews, questionnaires, focus group discussions, and participatory action research to conduct the study. There were 40 participants in the qualitative part which consisted of community leaders, tourism entrepreneurs, villagers, government officers, and private employees. This study also collected the data from the 385 tourists as the sample in the quantitative part. The statistical program was used to analyze the quantitative data and the qualitative data were categorized and set into the theme. The preliminary results of the research show that the tourists satisfied with the potential of tourism management of the community at an average level ( = 2.83). The classification of each side found that most tourists satisfied with tourism resources at an average level ( = 3. 26), infrastructure services, and tourism services at an average level ( = 3.04), and tourism marketing at an average level ( = 2.85) respectively. The guidelines in developing the community-based tourism management consisted of 1) providing the tourism resource information to facilitate tourists; 2) developing the potential of tourism personnel to be standardized and 3) establishing a coordination center to drive tourism management of the community.